2020
DOI: 10.1016/j.jcot.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Angular deformities of lower limb in children: Correction for whom, when and how?

Abstract: Angular deformities are common presentations in childhood and adolescent age group. It is important to differentiate a true deformity from a physiological deformity, this requires measurement of the intercondylar and intermalleolar distance. Once a true deformity is diagnosed, the apex of the deformity requires to be established. Lower limb frontal plane deformities are evaluated with a true AP standing radiographs of the entire lower limb from hip to ankle. Mechanical or anatomical axis calculation gives the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Therefore, sufficient growth was present to attain the desired correction. Gupta et al had suggested that to achieve a 20° correction, a minimum of 2 years of growth must be remaining [5]. On the contrary, hemiepiphysiodesis in a younger patient can cause a rebound deformity following the removal of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sufficient growth was present to attain the desired correction. Gupta et al had suggested that to achieve a 20° correction, a minimum of 2 years of growth must be remaining [5]. On the contrary, hemiepiphysiodesis in a younger patient can cause a rebound deformity following the removal of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have discussed the preliminary planning of high tibial osteotomy [14], [22]. Based on different osteotomy problems, the need for planning also varies.…”
Section: Discussionmentioning
confidence: 99%
“…The intersection of these straight lines involves mechanical [14], [15] or anatomical axes [16] It is also influenced by the need or regulation of the osteotomy itself i.e. varus gene defect [14], valgus [17] or recurvatum [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axis deviations in the coronal plane are commonly observed in developing children and are usually corrected by physiological mechanisms typical of growth ( 2 ) . However, when such deviations persist, they can lead to gait dysfunction, predisposing to joint changes such as chondropathy, instability, and, occasionally, early osteoarthritis ( 3 ) . Among the acquired causes of axis deviations in pediatric patients, trauma is the most common; trauma can cause deformities due to fractures, especially physeal or transphyseal fractures, repetitive stress on the growth plate, or osteochondral injuries ( 1 ) .…”
Section: Introductionmentioning
confidence: 99%